The First into the Dark The Nazi Persecution of the Disabled - Robertson, Michael (2019)
"Under the Nazi regime a secret program of 'euthanasia' was undertaken against the sick and disabled. Known as the Krankenmorde (the murder of the sick) 300,000 people were killed. A further 400,000 were sterilised against their will. Many complicit doctors, nurses, soldiers and bureaucrats would then perpetrate the Holocaust. From eyewitness accounts, records and case files, The First into the Dark narrates a history of the victims, perpetrators, opponents to and witnesses of the Krankenmorde, and reveals deeper implications for contemporary society: moral values and ethical challenges in end of life decisions, reproduction and contemporary genetics, disability and human rights, and in remembrance and atonement for the past."